Seismic performance and design of precast concrete building structures: an overview - Khare, R. K.; Maniyar, M. M.; Uma, S.R.; Bidwai, V. B. (Journal of Structural Engineering, 2024)
Seismic performance and behaviour of precast concrete structures which were not designed and detailed as per existing provisions in relevant standards was very poor during past earthquakes while the buildings constructed and designed incorporating seismic design concepts performed remarkably well. A brief review of seismic performance and design of precast concrete systems is presented to seek for the ways to improve and develop construction of precast concrete structures in India. This paper brings together the historical perspective on the performance of precast concrete structures so that lessons can be learnt to avoid the poor performance of these systems. An extensive literature on experimental studies has been also reported here to demonstrate the improved seismic performance of precast concrete systems. Further, a review and comparison of International code provisions on the design and construction of precast concrete systems is presented to help in developing the provisions and practice of these systems in Indian perspective. Identification of areas that need revision or attention in the current IS Code provisions are attempted in the light of International practice.